The exemplary poetry of Geoffrey Hill: authority and exemplarity in A Treatise of Civil Power - Vincent, Bridget (Modern Humanities Research Association, 2015)
Geoffrey Hill's ethical anxieties turn on a tension between aesthetic autonomy and engagement with the polis, a tension illuminated by his adumbration of an exemplary poetics. ‘Exemplarity’ is characterized by a similar tension between intransitive and transitive activity, so that a poem can be ‘exemplary’ through its independent merit but also because it influences others. Exemplarity has become especially significant in Hill's ‘late style’: his intensifying rehearsals of despair at the degradation of public language have made the models offered by figures from the past (and the exemplary influence of his own work) an increasingly revealing element in his writing.